The origins of monetary policy disagreement: The role of supply and demand shocks - Madeira, C.; Madeira, J.; Monteiro, P. S. (Review of Economics and Statistics, 2026)
We investigate how dissent in the Federal Open Market Committee (FOMC) is affected by structural macroeconomic shocks obtained using a medium-scale dynamic stochastic general equilibrium model. We find that dissent is less (more) frequent when demand (supply) shocks are the predominant source of inflation fluctuations. In addition, supply shocks are found to raise private sector forecasting uncertainty about the path of interest rates. Since supply shocks impose a tradeoff between inflation and output stabilization while demand shocks do not, our findings are consistent with heterogeneous preferences over the dual mandate among FOMC members as a driver of policy disagreement.